Safety and efficacy of intravenous thrombolytic treatment in wake‐up stroke: Experiences from a single center - Wiśniewski, Adam (Brain and behavior, 2021)
Objectives Wake‐up stroke is an important clinical problem that may account for a quarter of all ischemic strokes. This study aimed to establish the safety and efficacy of intravenous thrombolytic treatment of wake‐up strokes by comparing it to the standard thrombolysis treatment in strokes with clear onsets and wake‐up strokes that did not receive reperfusion therapy. Methods This retrospective study enrolled 95 patients with ischemic strokes who underwent thrombolytic treatment with alteplase, including nine patients with wake‐up strokes. The safety profile (mortality and intracranial bleeding) and efficacy (clinical and functional outcomes on admission, discharge, and 90 days after stroke onset) were evaluated. Results When assessed using the modified Rankin scale (mRs), the patients with wake‐up strokes had significantly more favorable functional outcomes on discharge when compared to those who received standard thrombolysis (p = .0289). No significant differences were noted when the favorable outcome rate (mRs score = 0–2) at three months post‐thrombolysis (Odds ratio [OR] = 2.07; 95% confidence interval [CI] = 0.41–10.6; p = .3807) and safety outcomes (death during hospitalization: OR = 0.49; 95% CI = 0.03–9.11; p = .6295 and intracranial bleeding 24 hr after treatment: OR = 0.43; 95% CI = 0.02–7.58; p = .5707) were compared between the two groups. The Cochran–Mantel–Haenchel shift analysis showed a significantly more favorable distribution of the mRs scores at three months after the stroke onset in the patients with wake‐up strokes who were treated with alteplase compared to those who did not receive thrombolysis (OR = 1.42; 95% CI = 1.01–1.82; p = .0426). Conclusions Our study demonstrated that in patients who awaken with stroke symptoms, intravenous thrombolytic treatment is a safe procedure that may lead to favorable outcomes. Further studies should be performed to increase the size of the group of patients with wake‐up strokes who can be treated with reperfusion therapy. The aim of the study was to establish the safety and efficacy of intravenous thrombolytic treatment in wake‐up stroke comparing to the standard thrombolysis treatment in stroke with clear onset. Wake‐up stroke subjects were characterized by significantly more favorable functional outcome on discharge in contrast to the standard thrombolysis procedure subjects (p = .0289). Our study showed that intravenous thrombolytic treatment is a safe procedure and may lead to a favorable outcome in subjects who are awaken with stroke symptoms.